PERAN PEREMPUAN DALAM UPACARA KENDURI SKO PADA MASYARAKAT KERINCI - Sean Popo Hardi; Mohd. Norma Sampoerno; Maratun Saadah (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2021)
Kerinci is one of the regions in Sumatra with a strong matrilineal culture. This is reflected in the customs that place the role of women more dominant than men as contained in kenduri Sko ceremony activities. This research aims to see how the role of women contained in the traditional ceremony of Kenduri Sko. This study is a qualitative descriptive study that seeks to explain the representation of matrilineal culture through the role of women in the indigenous upara Kenduri Sko. The results showed that the dominance of women in the largest ceremony for Kerinci society, Kenduri Sko, was very dominant. It is seen from the role of women as dayangs in the series of